Intermediates and reaction pathways from the degradation of microcystin-lr with sulfate radicals - De La Cruz, Armah A.; Dionysiou, Dionysios Demetriou D.; Antoniou, Maria G. (My University, 2010)
Degradation of the cyanotoxin microcystin-LR (m/z 995.5) using sulfate radical-based advanced oxidation technologies (AOTs) and identification of reaction intermediates formed during treatment were investigated in this study. To the best of our knowledge this is the first study on the degradation and identification of reaction intermediates for any cyanotoxin with SO4•−. Tandem mass spectrometry designated the formation of nine (as m/z) reaction intermediates with four of them (m/z 1011.5, 1027.5, 1029.5, and 1045.5) having multiple peaks in the TIC chromatogram. New peaks that were not observed with hydroxyl radical formed during photocatalytic oxidation (PCO) have been detected such as m/z 1045.5. The initially formed intermediates involved the oxidation of the unsaturated bonds of MC-LR especially the diene bonds located on the chain of the Adda amino acid. Subsequent intermediates implicated the oxidative cleavage of small functional groups (i.e., —COOH), up to the complete removal of the Adda chain. The electrophilic character of SO4•− is proven by the multihydroxylation of the aromatic ring. Toward the end of treatment, simultaneous oxidation of the Adda chain and the cyclic structure occurred without the formation of linear products.
Keywords: Degradation; Radical; Activated persulfate